EVALUASI KEBERHASILAN WEBSITE PEMERINTAH DAERAH KABUPATEN REJANG LEBONG DENGAN METODE ITPOSMO - Andang Wijanarko; Ema Utami; Henderi Henderi (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
The website also serves as a tool or a tool for implementing e-government. The use of media websites is one way to realize a clean government, transparent and authoritative or known good governance. This study uses ITPOSMO approach to assess the success rate of the district local government website Rejang Lebong. Model ITPOSMO considered appropriate to evaluate the implementation of e-government for using the approach of the seven dimensions, namely information, technology, processes, objectives and values, staffing and skills, management systems and structures, other resources (time and money) in assessing the success or failure of a e-government projects. The results of this study indicate that the local government website Rejang Lebong district declared a failure in implementing e-government with a value gap scoring 38.12. Of the seven dimensions evaluated, staffing and skill dimension is the dimension of the lowest levels of his gap of 2.5, and the dimensions of the resource: time and money into the greatest dimension of its value gap that is equal to 7.85. Keywords: Website, E-government, ITPOSMO